2023
DOI: 10.3390/microorganisms11020459
|View full text |Cite
|
Sign up to set email alerts
|

High-Molecular-Weight Plasmids Carrying Carbapenemase Genes blaNDM-1, blaKPC-2, and blaOXA-48 Coexisting in Clinical Klebsiella pneumoniae Strains of ST39

Abstract: Background: Klebsiella pneumoniae, a member of the ESKAPE group of bacterial pathogens, has developed multi-antimicrobial resistance (AMR), including resistance to carbapenems, which has increased alarmingly due to the acquisition of carbapenemase genes located on specific plasmids. Methods: Four clinical K. pneumoniae isolates were collected from four patients of a neuro-intensive care unit in Moscow, Russia, during the point prevalence survey. The AMR phenotype was estimated using the Vitec-2 instrument, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The isolate UTA41 co-harbor the OXA-10-type class D β-lactamase and the KPC-2-type class A β-lactamase. This co-carriage was observed on different studies of Klebsiella pneumoniae from clinical origin on Sweden, Taiwan, and Russia [ [34] , [35] , [36] ]. KPC-2 has become the most clinically important carbapenemases enzyme due to its prevalence in enteric bacteria from human, animal and environmental origin [ [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 62%
“…The isolate UTA41 co-harbor the OXA-10-type class D β-lactamase and the KPC-2-type class A β-lactamase. This co-carriage was observed on different studies of Klebsiella pneumoniae from clinical origin on Sweden, Taiwan, and Russia [ [34] , [35] , [36] ]. KPC-2 has become the most clinically important carbapenemases enzyme due to its prevalence in enteric bacteria from human, animal and environmental origin [ [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 62%
“…Since the DNA is usually isolated from patient samples like rectal swabs or stool, which contain only a limited number of the bacteria of interest, the chosen DNA extraction method should be very efficient. In addition, carbapenem resistance genes are often encoded on medium to large low-copy plasmids [19,20,50,51], but can also be found on the bacterial chromosome [18]. Besides that, species-specific genes used as targets, like khe in the case of K. pneumoniae, are also located on the bacterial chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also included the recently reported four ST39 isolates carrying both bla KPC-2 and bla VIM-1 [ 21 ]. Recently, Kuzina et al highlighted the concurrent isolation of bla NDM-1 , bla KPC-2 , and bla OXA-48 in ST39 CRKP isolates [ 49 ]. Three CRKP isolates (12.5%) were assigned to ST323; sporadic cases of ST323 CRKP have been previously reported in Greece and other European countries [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%